2011
DOI: 10.1089/brain.2011.0029
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Tongue Stimulation Normalizes Activity Within the Motion-Sensitive Brain Network in Balance-Impaired Subjects as Revealed by Group Independent Component Analysis

Abstract: Multivariate analysis of functional magnetic resonance imaging (fMRI) data allows investigations into network behavior beyond simple activations of individual regions. We apply group independent component analysis to fMRI data collected in a previous study looking at the sustained neuromodulatory effects of electrical tongue stimulation in balance-impaired individuals. Twelve subjects with balance disorders viewed optic flow in an fMRI scanner before and after 5 days of electrical tongue stimulation. Nine heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
(82 reference statements)
2
23
0
Order By: Relevance
“…This change can be considered a decrease in the weighting of visual motion input to the balance-processing network, consistent with other analyses of this data that showed reduced activation of hMT + after CN-NINM (Wildenberg et al, 2011b). In particular, this change will result in less PIVC deactivation in response to motion-no longer do strong visual stimuli suppress processing of other sensory modalities (Dieterich and Brandt, 2000;Fetsch et al, 2009;Mahboobin et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This change can be considered a decrease in the weighting of visual motion input to the balance-processing network, consistent with other analyses of this data that showed reduced activation of hMT + after CN-NINM (Wildenberg et al, 2011b). In particular, this change will result in less PIVC deactivation in response to motion-no longer do strong visual stimuli suppress processing of other sensory modalities (Dieterich and Brandt, 2000;Fetsch et al, 2009;Mahboobin et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…GLM-based fMRI studies have found increased activation of hMT + in these subjects in response to optic flow, consistent with the idea that sensory loss in one modality can produce a compensatory increase in the sensitivity of another (Curthoys and Halmagyi, 1995;Dieterich et al, 2007;Wildenberg et al, 2010Wildenberg et al, , 2011b. These connectivity findings support the hypothesis that the motion-sensitive visual cortices are hypersensitive to information arriving from the primary visual cortex.…”
Section: Discussionsupporting
confidence: 83%
“…TDU or TDU-like tongue stimulation delivered simultaneously with balance and gait exercises, even if the tongue stimulus is not linked to head, plantar or any other kinds of sensor, appears to yield both long-term symptom reduction as well as measureable changes in brain activity [8490,100,101]. This new method, which is not sensory substitution, but which may, if desired, be combined with sensory substitution, has been dubbed Cranial-Nerve Non-Invasive Neuromodulation (CN-NINM) and is under investigation at the Tactile Communication and Neurorehabilitation Lab (TCNL) at the University of Wisconsin–Madison.…”
Section: Selected Applicationsmentioning
confidence: 99%
“…Wildenberg et al (2010) showed that stimulation that doesn't convey information about body posture or gravity can improve balance performance in people with balance dysfunction [102]. They've also investigated the effects of electrotactile tongue stimulation on balance performance and have used imaging techniques such as MRI and fMRI to show that stimulation upregulates visual sensitivity to optic flow in people with balance impairments [102][103][104][105].…”
Section: Mechanismmentioning
confidence: 99%